2016
DOI: 10.1177/0961000616666129
|View full text |Cite
|
Sign up to set email alerts
|

The impact of better access to scientific journals on the quality of research work: The case of a small university

Abstract: Linking a publication with scientific research results and the use of information resources is a key component of the collection, development and assessment of an academic library. Librarians often use quantitative data, but it is not easy to come by. Directly connecting library and information services to the impact they have can be quite difficult. Focusing on the 2010–2014 period, we have linked the quality and quantity of published papers to usage statistics for the newly acquired consortia access to schol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…In this group, providing sufficient e-resources is critical to facilitate scholarly work. Another study indicated that better accessibility to quality information resources leads to an increase in publication quality (Miholič and Južnič, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In this group, providing sufficient e-resources is critical to facilitate scholarly work. Another study indicated that better accessibility to quality information resources leads to an increase in publication quality (Miholič and Južnič, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…This supports the assertions of Ogunniyi, Akerele and Afolabi (2011) and Cottrell (2013) who opine that journals are useful for completing thesis and dissertations. Miholič and Južnič (2016) assert that journals are the basis for scientific research and communication. Afful-Broni, Owusu-Ansah and Takyi (2016) find in their study that graduate students use journals for their research projects.…”
Section: Discussion Of Findingsmentioning
confidence: 99%
“…Finally, librarians must demonstrate the legacy advantage of print serials, as opposed to electronic serials which are subject to the pitfalls of technology (Dilevko and Gottlieb, 2002). Librarians must, therefore, enhance and increase their print serial collection as increased access to scholarly resources leads to improved research output of researchers (Miholič & Južnič, 2016).…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
“…Miholič and Južnič (2018) analysed the participation of a university in three consortia for access to electronic e-journals through the use of available resources. This study identified that there was an increase in the number of articles published by researchers linked to the consortium Institution, thus demonstrating an effective result of this participation.…”
Section: The Consortium In the Library Contextmentioning
confidence: 99%